Evaluation of the Impact of Near-Infrared Multiwavelength Locked System Laser Therapy on Skin Microbiome in Atopic Dogs - Sara Muñoz Declara; Aldo D’Alessandro; Agnese Gori; Benedetta Cerasuolo; Sonia Renzi; Michele Berlanda; Eric Zini; Monica Monici; Duccio Cavalieri; Giordana Zanna (Animals, 2024)
Photobiomodulation (PBM) is a newly adopted consensus term to replace the therapeutic application of low-level laser therapy. It has been suggested that PMB influences the microbiome which, in turn, has increasingly been shown to be linked with health and disease. Even though the use of PBM has also grown dramatically in veterinary medicine, there is still a lack of evidence supporting its effect in vivo. Our objective was to investigate the impact of a dual-wavelength near-infrared laser source (Multiwavelength Locked Laser System, MLS®) on the skin microbiome in atopic dogs. Twenty adult-client-owned atopic dogs were enrolled in the study. The dogs were treated with MLS® laser therapy on one half of the abdominal region, whereas the contralateral side was left untreated and served as a control. Skin microbiome samples were collected before and after MLS® treatments, and then subjected to NGS-based ITS and 16S rRNA analysis. The results showed that while microbiome composition and diversity were not significantly affected, PBM could play a role in modulating the abundance of specific bacterial species, in particular Staphylococcus, that represent a major skin pathogenic strain. To the best of the authors’ knowledge, this is the first study to investigate the potential impact of MLS® laser therapy on the skin microbiome in atopic dogs.